The Effect Using Wordwall Game Applications To Improve Student’s Vocabulary In Chumchon Ban Phanokkhao School - Rizka amalia Az Zahrah; Khoirul Anwar (Universitas Muhammadiyah Gresik, 2023)
This study aims to determine the effectiveness of the wordwall application used by students to increase English vocabulary. This type of research uses quantitative methods with research subjects of class VII, VIII and IX involving 30 students. The data collection method was carried out through pre-test, treatment, and post-test. Analysis of the data presented in this study by comparing the values ​​of the pre-test and post-test (paired sample t test). The results of this study are; (1) there is a significant difference means from pretest and posttest for each class VII (pre = 75.00, post = 92,27), VIII (pre = 78,57, post = 92,14), IX (pre = 76,92, post = 90,00); (2) there is a difference in the average pretest and posttest learning outcomes with a sig value of 0.000 is less than 0.05 (0.000 < 0.05). It concludes that the wordwall application is effective in increasing English vocabulary. In addition, wordwall applications can increase mastery of vocabulary because of the simple steps. So, it might enhance enthusiasm in learning English vocabulary.